2020
DOI: 10.1186/s43054-020-00030-2
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and metabolic pattern in obese Egyptian children: its association with C-reactive protein

Abstract: Background Obesity is the most common chronic metabolic disease in children. The global prevalence of obesity has doubled from 1990 to 2015. Worryingly, the increase is more in children than adults. It has reached epidemic ranges and is a significant global problem. High-sensitivity C-reactive protein (hs-CRP) is a parameter that is used to assess inflammation and risk factor for cardiovascular events. Some reports describe an association between hs-CRP and obesity. The objective of the study is to evaluate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…Our work revealed that no substantial variation was existed among obesity in children and controls in SBP and DBP (mmHg) and this agreed with Mohamed et al, [17] study. While Tanaka et al [18] discovered that obesity in children substantially greater in diastolic and systolic blood pressure contrasted to their controls.…”
Section: Discussionsupporting
confidence: 93%
“…Our work revealed that no substantial variation was existed among obesity in children and controls in SBP and DBP (mmHg) and this agreed with Mohamed et al, [17] study. While Tanaka et al [18] discovered that obesity in children substantially greater in diastolic and systolic blood pressure contrasted to their controls.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the lipid profile in our work before therapy, in both obese groups A and B, total cholesterol, LDL-C, and triglyceride level was significantly increased, and the HDL-C level was significantly reduced than those of controls. Our results agreed with Nogueira-de-Almeida and Mello, Milyani and Al-Agha, and Mohamed et al [39][40][41]. After therapy in groups A and B, the levels of total cholesterol, LDL-C, and triglycerides decreased significantly and became lower than before the intervention, while the level of HDL-C increased and became higher than before the therapy.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of dyslipidemia among obese children was estimated at 48.8% in studies from Europe and 63% in studies from South America [ 46 ]. We found higher levels of serum LDL-C and triglycerides and a lower HDL-C level in obese and overweight children as compared to the normal weight group, thus confirming findings from previous studies [ 9 , 10 , 19 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 91%